Algebra Worksheets 4

In this topic algebra worksheets 4 you can find 6 questions in the form of quiz.You can also find the answers also.Students who are practicing algebraic identity must attend this test to test their knowledge.

These question paper is mainly prepared for 8th,9th and 10th grade students.You can click the link answer to get direct answer without taking test.You are given the problems based on the second formula that is (a-b)³ .

1. Expand (x - 2y) ³

(A) x³ + 6 x² y - 6 xy² + 8 y³

(B) x³ - 6 x² y + 12 xy² - 8 y³

(C) 2x³ + 6 x² y + 6 xy² + 8 y³

2. Expand (2a - b) ³

(A) 8a³ - 12 a² b + 6a b² - b ³

(B) 8a³ + 12 a² b + 6a b² + b ³

(C) 8a³ + 12 a² b + 6a b² - b ³

3. Expand (3S - T) ³

(A) 27S³ - 27 S² T + 9 ST ² - T ³

(B) 8S³ + 24 S² T + 2S T ² + T ³

(C) S³ + 9S² T - 64 S T ² + T ³

4. Expand (V - 5Q) ³

(A) V ³ -15 V ² Q + 75 V Q² - 125 Q³

(B) 27 V ³ - 2 V ² Q + 3 V Q² - Q³

(C) 27 V ³ - 2 V ² Q + 3 V Q² - Q³

5.Expand (4T - Q) ³

(A) 64T³ - 96 T² Q - 108 T Q² + Q ³

(B) 64T³ - 96 T² Q + 108 T Q² - Q ³

(C) 64T³ - 48 T² Q + 12 T Q² + Q ³

6. Expand (5p - q) ³

(A) p ³ - 15 p² q + 75 p q ² - 125 q³

(B) p ³ - 15 p² q + 75 p q ² + 125 q³

(C) 125 p³ - 75 p² q + 15 p q ² + q³

These are the question prepared in the topic Algebra worksheets 4

1. x³ - 6 x² y + 12 x y² - 8 y³

2. 8 a³ - 12 a² b + 6a b² - b ³

3. 27 S³ - 27 S² T + 9 ST ² - T ³

4. V ³ -15 V ² Q + 75 V Q² - 125 Q³

5. 64 T³ - 48 T² Q + 12 T Q² + Q ³

6. 125 p ³ - 75 p² q + 15 p q ² + q³

 Solution for question 1 jQuery UI Accordion - Default functionality .ui-widget-overlay,.ui-state-disabled,ui-button{background:#fff;border:1px solid #fff;color:#b9cd6d;font-weight:bold} (a - b)3 = a3 - 3 a2 b + 3 a b2 - b3 here a = x and b = 2y (x - 2y)2 = x2 - 3 x2 (2y) + 3 x (2y)2 - (2y)3                     = x2 - 6 x2 y + 3 x (22y2) - (23y3)                     = x2 - 6 x2 y + 3 x (4y2) - (8 y3)                     = x2 - 6 x2 y + 12 x y2 - 8 y3 Solution for question 2 jQuery UI Accordion - Default functionality .ui-widget-overlay,.ui-state-disabled,ui-button{background:#fff;border:1px solid #fff;color:#b9cd6d;font-weight:bold} (a - b)3 = a3 - 3 a2 b + 3 a b2 - b3 here a = 2a and b = b (2a - b)3 = (2a)3 - 3 (2a)2 (b) + 3 (2a)(b)2 - (b)3                     = (23a3) - 3 (22a2) (b) + 3 (2a)(b)2 - (b)3                     = 8 a3 - 3 (4 a2) (b) + 6 a b2 - b3                     = 8 a3 - 12 a2b + 6 a b2 - b3 Solution for question 3 jQuery UI Accordion - Default functionality .ui-widget-overlay,.ui-state-disabled,ui-button{background:#fff;border:1px solid #fff;color:#b9cd6d;font-weight:bold} (a - b)3 = a3 - 3 a2 b + 3 a b2 - b3 here a = 3S and b = T (3S - T)3 = (3S)3 - 3 (3S)2 (T) + 3 (3S)(T)2 - (T)3                     = (33S3) - 3 (32S2) (T) + 3 (3S)(T)2 - (T)3                     = 27 S3 - 3 (9 S2) (T) + 3 (3S)(T)2 - (T)3                     = 27 S3 - 27 S2T + 9 S T2 - T3 Solution for question 4 jQuery UI Accordion - Default functionality .ui-widget-overlay,.ui-state-disabled,ui-button{background:#fff;border:1px solid #fff;color:#b9cd6d;font-weight:bold} (a - b)3 = a3 - 3 a2 b + 3 a b2 - b3 here a = V and b = 5Q (V - 5Q)3 = (V)3 - 3 (V)2 (5Q) + 3 (V)(5Q)2 - (5Q)3                     = V3 - 3 V2 (5Q) + 15 V Q2 - (53Q3)                     = V3 - 15 V2 Q + 15 V Q2 - 125 Q3 Solution for question 5 jQuery UI Accordion - Default functionality .ui-widget-overlay,.ui-state-disabled,ui-button{background:#fff;border:1px solid #fff;color:#b9cd6d;font-weight:bold} (a - b)3 = a3 - 3 a2 b + 3 a b2 - b3 here a = 4T and b = Q (4T - Q)3 = (4T)3 - 3 (4T)2 (Q) + 3 (4T)(Q)2 - (Q)3                     = (43T3) - 3 (42T2)(Q) + 3 (4T)Q2 - Q3                     = 64 T3 - 3 (16 T2)(Q) + 12 T Q2 - Q3                     = 64 T3 - 48 T2Q + 12 T Q2 - Q3 Solution for question 6 jQuery UI Accordion - Default functionality .ui-widget-overlay,.ui-state-disabled,ui-button{background:#fff;border:1px solid #fff;color:#b9cd6d;font-weight:bold} (a - b)3 = a3 - 3 a2 b + 3 a b2 - b3 here a = 5p and b = q (5p - q)3 = (5p)3 - 3 (5p)2 (q) + 3 (5p)(q)2 - (q)3                     = (53p3) - 3 (52p2) (q) + 15 p q2 - q3                     = 125 p3 - 3 (25p2) (q) + 15 p q2 - q3                     = 125 p3 - 75 p2q + 15 p q2 - q3